Effect of perception of sustainability in local food experiences on healthy eating tendency: mediator and moderator effects - Aksakallı Bayraktar, Zühal; Oral, Serhan; Bulut, Samuray Hakan; Bayraktar, Yusuf (Frontiers in Nutrition, 2023)
Tourists who favor local food typically care about healthy food choices. Their view of locally produced food as healthy is related to perceptions of sustainability. This relationship can be explained by tourists’ personality traits and their tendency to eat local food. The research aimed to reveal the effect of tourists’ perceptions of sustainability in the context of local food experiences on healthy eating tendencies. In addition, we aimed to determine the role of tourists’ personality traits and local eating tendencies, and elucidate the moderating role of online information searching about food choices. An online questionnaire (via e-mail and WhatsApp) was used to obtain data from 379 research participants, recruited using a non-probabilistic sampling technique. A research model and hypotheses were formed based on Hayes PROCESS Macro models 90 and 6, and moderator and mediator effects were analyzed using these models. Healthy eating was well-explained by the model, and the perception of social and environmental sustainability in local food experiences (LFE-SES) positively affected food-related personality traits (FRPT), local food eating tendencies (LFET), and healthy eating (HE). While food-related personality traits do not serve as mediators in the relationship between the perception of sustainability and healthy eating, local food eating tendency plays a mediating role in this relationship. In addition, when food-related personality traits and local food eating tendency were evaluated together, they had a mediating role in the aforementioned relationship. Online information searching had an insignificant moderating effect. The findings help promote understanding of healthy eating tendencies, and within the local food context, they have critical theoretical and practical implications for the relationship between the perception of sustainability, food-related personality traits, local food eating tendencies, and healthy eating.